Analisis Efektivitas Strategi Pemasaran melalui Media Sosial terhadap Penjualan Online Produk Makanan di Kutacane Kabupaten Aceh Tenggara - Maufira , Rila (Trending: Jurnal Manajemen dan Ekonomi, 2023)
Social media can be used for business communication, product and service marketing, customer and supplier communication, brand enhancement, cost reduction, and online sales. The purpose of this study was to determine and analyze the effectiveness of social media marketing strategies on online food product sales in Kutacane, Southeast Aceh Regency. This study used a quantitative descriptive research method. The population used in this study was 1. The method used was quantitative descriptive research by distributing questionnaires. This research was measured using a Likert scale. The collected data were analyzed using SPSS software, consisting of descriptive statistical tests, classical assumption tests, multiple linear regression, simultaneous and partial hypothesis tests, and coefficients of determination. The results showed that social media attention had a positive and significant effect on online food product sales in Kutacane, Southeast Aceh Regency. This indicates that social media attention significantly increases online sales of food products in Kutacane, Southeast Aceh Regency. Social media interest has a positive and significant effect on online sales of food products in Kutacane, Southeast Aceh Regency. This indicates that social media interest contributes to increasing online sales of food products in Kutacane, Southeast Aceh Regency. The adjusted R-square value is 0.646, indicating that the variables social media attention and social media interest can explain 64.6% of the variation in online sales of food products in Kutacane, Southeast Aceh Regency, while the remaining 35.4% is explained by independent variables not examined, such as service quality and brand.